Beyond the Corporate Veil a commentary on the approach of the South African Courts to the question of lifting the corporate veil, with particular reference to a tax-avoidance based structure in common use in South Africa at this time - Perrins, R H (Department of Commercial Law, 2021)
"The Court of Appeal has declared that the formation of the respondent company and the agreement to take over the business of the appellant were a scheme "contrary to the true intent and meaning of the Companies Act". I know of no means of ascertaining what is the intent and meaning of the Companies Act except by examining its provisions and finding what regulations it has imposed as a condition of trading with limited liability .... we have to interpret the law, not make it." Salomon v Salomon & Co Ltd, per Herschell, LJ. Thus the starting point of the court in this seminal case (which has been followed ever since in regard to corporate personality) was to interpret the law as they found it in the Act - if the formalities had been complied with a separate judicial person came into being: 2 "The Company is at law a different person altogether from the subscribers to the memorandum; and, although it may be that after incorporation the business is precisely the same as before, and the same persons are managers, and the same hands receive the profits company is not in law the agent of the subscribers or trustee for them".